A prospective observational study to evaluate the role of restaging transurethral resection of bladder tumour in patients with non-muscle invasive bladder cancer - Raj, Kishan K.; Taneja, Yogesh; Ramdev, Prateek; Dhaked, Santosh K.; Singh, Charan K.; Shekar, Ashwin P. (International Journal of Research in Medical Sciences, 2019)
Background: Transurethral resection of bladder tumour (TURBT) is the primary treatment modality for Non-muscle invasive bladder cancer (NMIBC). Restaging transurethral resection of bladder tumour (RETURBT) is indicated to reduce risk of residual disease and correct staging errors after primary TURBT. The aim of the study is to evaluate the risk of residual tumour and upstaging in NMIBC after TURBT and to investigate the risk factors for the same. Methods: A prospective observational study was carried out over 4 years and 87 patients were included in the study. Patients with NMIBC underwent RETURBT after 2-6 weeks of primary TURBT. The incidence of residual tumour and upstaging in RETUBRT was correlated with various histopathological and morphological parameters in primary TURBT. Results: Out of 87 patients, who underwent RETURBT, residual disease was present in 51 patients (58.6%) and upstaging occurred in 22 patients (25.2%).On univariate analysis, T1 stage (p=0.01), high grade (p=0.01), Carcinoma in situ(CIS) (p=0.01) and multifocality (p=0.05) were predictive for residual disease in RETURBT. High grade (p=0.01), CIS (p=0.01) and absence of detrusor muscle in specimen (p=0.03) were risk factors for upstaging in RETURBT. Conclusions: NMIBC have high incidence of residual disease and upstaging after primary TURBT. T1 stage, high tumour grade, CIS, and multifocality are risk factors for residual disease after primary TURBT. High tumour grade, CIS and absence of detrusor muscle are strongly associated with upstaging during RETURBT.